2018 IEEE Nuclear &Amp; Space Radiation Effects Conference (NSREC 2018) 2018
DOI: 10.1109/nsrec.2018.8584264
|View full text |Cite
|
Sign up to set email alerts
|

NASA Goddard Space Flight Center's Compendium of Recent Single Event Effects Results

Abstract: We present the results of single event effects (SEE) testing and analysis investigating the effects of radiation on electronics. This paper is a summary of test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Low energy protons (fluence of 1.45⋅10 14 cm -2 ) lead to the complete degradation of silicon power diodes, similar to the effects of much higher γ-ray fluences (4.25⋅10 20 cm -2 ). Experiments have shown that electron and neutron radiations are less harmful than protons and γ-rays [102], although with some vulnerability, such as the case of the Infineon TM BAR64-05 E6327 RF PIN diode [103]. In summary, in terms of fluence, diode failure typically occurs around 1⋅10 14 cm -2 for 1 MeV protons, roughly 1⋅10 17 cm -2 for 100 MeV protons, and over 1⋅10 20 cm -2 for γ-rays [104].…”
Section: A Diodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Low energy protons (fluence of 1.45⋅10 14 cm -2 ) lead to the complete degradation of silicon power diodes, similar to the effects of much higher γ-ray fluences (4.25⋅10 20 cm -2 ). Experiments have shown that electron and neutron radiations are less harmful than protons and γ-rays [102], although with some vulnerability, such as the case of the Infineon TM BAR64-05 E6327 RF PIN diode [103]. In summary, in terms of fluence, diode failure typically occurs around 1⋅10 14 cm -2 for 1 MeV protons, roughly 1⋅10 17 cm -2 for 100 MeV protons, and over 1⋅10 20 cm -2 for γ-rays [104].…”
Section: A Diodesmentioning
confidence: 99%
“…In contrast, SEE testing reveals vulnerabilities in certain diode types. While many devices exhibit no SEE occurrence, including high-speed switching diodes such as the onsemi TM MMBD1501A and the NXP TM BAS16,215, as well as some Schottky types like the onsemi TM NSR0140P2T5G, others degrade during testing, such as the Infineon TM BAR64-05 E6327 RF PIN diode [103]. This indicates varying levels of susceptibility and highlights the need for protective measures.…”
Section: A Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in [48] studied the SEE susceptibility of an AS008MA12A-C1SC, an 8-Mb STT-MRAM, under heavy ions. SEFIs with large numbers of bitflips happened at a LET of 1.84 MeV•cm 2 /mg and higher; however, they disappeared with a power cycle.…”
Section: ) Radiation Effects On Mramsmentioning
confidence: 99%
“…[88],[93].B. Oxide-Based Resistive RAM Oxide-based resistive switching RAM (OxRAM), often abbreviated ReRAM, RRAM, or OxRAM, is a two-terminal resistive device which uses the electrically induced resistance modulation due to vacancy motion in metal oxides as the basis of memory.…”
mentioning
confidence: 99%